Design UWB antenna for radar application - Qalib, Mohamed Ahmed (2021)
This project has investigated the proposed research about Ultra-wideband (UWB) antenna and its related aspects. The project work has been started with an introductory to UWB technology and its merits. The two most attractive merits of UWB are: high data rate communication and low power density. Radar is a classic example of an electronic engineering system that utilizes many of the specialized elements of technology practiced by electrical engineers, including signal processing, data processing, waveform design, electromagnetic scattering, detection, parameter estimation, information extraction, antennas, propagation transmitters, and receivers. The objectives of the project is based on the following consecutive steps, first to design and simulate UWB antenna for radar application. Secondly, to investigate antenna performance using reflector in order to achieve a high bandwidth. Thirdly, to design reflector in order to achieve high gain antenna. In this study, the designed antenna has offered excellent performance for lower-band frequency of UWB range, ranging from 3.1 GHz to 10.6 GHz. The antenna exhibits a -10 dB return loss bandwidth over the entire frequency band. The antenna is designed on FR4 substrate and fed with 50 ohms transmission line. The antenna with reflector design proposed in this report can provide ultra-wide bandwidth with nearly directional radiation patterns and satisfactory time domain performances which make them very suitable for the future radar applications.